Use of Soft Contact Lens for Esthetic and Functional Rehabilitation - de Paula Yoneda, Patrícia; Schellini, Silvana A.; Padovani, Carlos R.; Silva, Virgílio F (Wolters Kluwer, 2021)
OBJECTIVE: To report the outcomes and complications of colored soft contact lenses (SCLs) to improve esthetic or eye function in visually impaired (VI) or blind patients. METHODS: This retrospective study enrolled consecutive patients with unilateral or bilateral VI or blindness who had received colored SCLs to improve appearance or ocular function. Data were collected on demographics, complaints, complete ophthalmological examinations, types of SCL, follow-ups, and complications. RESULTS: The study sample was comprised of 109 patients (ages 4-80 years). Eighty-six patients (78.89%) had unilateral blindness, and 14 patients (12.84%) had functional disorder. Most of the patients presenting for improved esthetic had anterior segment pathology (74/67.88%), mainly secondary to trauma (55/50.5%) resulting in leukoma (73/66.97%). Patients with functional VI (19/17.43%) received filtered SCLs for color blindness (7/6.42%), diplopia (7/6.42%), or photophobia (5/4.58%). No serious complications were observed in any cases, and 94.49% of patients were satisfied with the SCLs. CONCLUSION: Colored SCLs can cover ocular surface imperfections in VI or blind eyes of patients who are seeking better cosmesis or improvement functional VI. Soft contact lenses with only one filter can cover imperfections of the ocular surface and improve vision in functional VI. Appropriate follow-up of these patients can reduce complication rates, resulting in good cosmesis and patient satisfaction with a positive impact on the lives of patients suffering from functional VI or blindness.